2020
DOI: 10.1111/jth.14897
|View full text |Cite
|
Sign up to set email alerts
|

Maximum 24‐hour platelet count fall: Metric for improving the diagnosis of heparin‐induced thrombocytopenia among patients with intermediate probability 4Ts scores

Abstract: Background: Most patients with suspected heparin-induced thrombocytopenia (HIT) and an intermediate probability 4Ts score do not have HIT. We aimed to develop a metric based on the rate of platelet count fall to aid in discriminating HIT status among patients with an intermediate 4Ts score. Methods:We derived a measure of the maximum 24-hour percentage decrease in platelet count (Fall max ) in a cohort of patients with suspected HIT and an intermediate 4Ts score at the University of Pennsylvania. We validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Compared with a slow decline in platelet counts, a rapid fall is more suggestive, as illustrated by the typical pattern of platelet count changes associated with HIT after cardiac surgery, 38 and as recently reported in a refinement of the 4 Ts score as well. 40 In our study, a platelet count decline ≥40%, whether over 3 days or over 6 days, was associated with HIT, but the strongest association was found for a platelet count decline ≥40% over 6 days. To further refine this item about the most suggestive pace, daily platelet counting would have been required, which is not currently recommended.…”
Section: F I G U R Ementioning
confidence: 39%
See 3 more Smart Citations
“…Compared with a slow decline in platelet counts, a rapid fall is more suggestive, as illustrated by the typical pattern of platelet count changes associated with HIT after cardiac surgery, 38 and as recently reported in a refinement of the 4 Ts score as well. 40 In our study, a platelet count decline ≥40%, whether over 3 days or over 6 days, was associated with HIT, but the strongest association was found for a platelet count decline ≥40% over 6 days. To further refine this item about the most suggestive pace, daily platelet counting would have been required, which is not currently recommended.…”
Section: F I G U R Ementioning
confidence: 39%
“…Of note, because clinical suspicion could arise in a somewhat delayed manner as discussed previously, such a decrease pace could be detected within the preceding 10 days. Compared with a slow decline in platelet counts, a rapid fall is more suggestive, as illustrated by the typical pattern of platelet count changes associated with HIT after cardiac surgery, 38 and as recently reported in a refinement of the 4 Ts score as well 40 . In our study, a platelet count decline ≥40%, whether over 3 days or over 6 days, was associated with HIT, but the strongest association was found for a platelet count decline ≥40% over 6 days.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Others have developed scores for particularly challenging patient populations like cardiopulmonary bypass patients who frequently have postoperative thrombocytopenia and nearly universal exposure to heparin (Lillo‐Le Louet score) 14 . Our group demonstrated that a more rapid platelet count fall in 24‐hours makes the diagnosis of HIT more likely in patients with an intermediate 4Ts score, and thus the rate of platelet count fall could be a useful tool following calculation of the 4Ts score to improve the positive predictive value of the score 15 . This approach and other modifications to the 4Ts score require validation in prospective studies.…”
Section: Clinical Diagnosis Of Hitmentioning
confidence: 91%